INHERITANCE RIGHTS OF CHILDREN UNDER WEDDING ACCORDING TO THE CIVIL CODE AND ITS IMPLICATIONS IN JUDICIAL PRACTICE - Arihadi Satriadi; Happy Lumban Gaol (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
This study discusses the inheritance rights of children born out of wedlock according to civil law and its implications in judicial practice. Under the Civil Code, children born out of wedlock only have a civil legal relationship with their mother and her family, while their inheritance rights to their biological father are very limited and can only be obtained if there is a valid acknowledgment. The distribution of inheritance for children born out of wedlock is also regulated differently from legitimate children, with a smaller proportion depending on the class of heirs inheriting simultaneously. However, Constitutional Court Decision No. 46/PUU-VIII/2010 expands the legal understanding by stating that children born out of wedlock may have a civil relationship with their biological father as long as it can be proven through science and technology or other evidence deemed valid under the law. This decision provides a legal basis for children born out of wedlock to access civil rights, including inheritance rights, in a more fair and equitable manner. This study shows that although there has been progress in recognizing the rights of children born out of wedlock, there are still normative and practical obstacles in its implementation, especially at the community and legal institution levels. Therefore, regulatory updates, legal awareness campaigns, and strengthening of evidence mechanisms and legal protection are needed to ensure that the principles of justice and non-discrimination toward children born out of wedlock are effectively realized within Indonesia's legal system.